We have a table that represents an exponential function.
We can express an exponential function as:
![y=a\cdot b^x](https://img.qammunity.org/2023/formulas/mathematics/high-school/6has3k4sb3pm3ew4419r8bw5p19fprxq7e.png)
We can use the values of the table to calculate the parameters "a" and "b".
For example we can use the value of y when x = 0 to calculate "a":
![\begin{gathered} y(0)=4 \\ a\cdot b^0=4 \\ a\cdot1=4 \\ a=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6filh5os4qwj4wak668q0cv781833uolqb.png)
We then can use two consecutive values to find the parameter "b":
![\begin{gathered} (y(2))/(y(1))=(a\cdot b^2)/(a\cdot b^1)=b^(2-1)=b \\ \Rightarrow b=(y(2))/(y(1))=(36)/(12)=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3x0uaz7b11omwcqraj1ljmt16sfn99zw4t.png)
Then, we can express the exponential function as:
![y=4\cdot3^x](https://img.qammunity.org/2023/formulas/mathematics/college/d6elmhmlcyaavnwixxhafdh1hkaopu7ph0.png)
Answer: y = 4*3^x